Effect of watermelon seed urease induced calcium carbonate precipitation (WSICP) on collapsible loess improvement based on unconfined compression and direct shear tests - Shuo Tu; Liping Zhu; Yuan Qin; Zhicheng Wang; Yating Zhu; Mingdong Li (Discover Sustainability)
Abstract The present study investigates how watermelon seed urease induced calcium carbonate precipitation (WSICP) technology enhances the mechanical properties of water-saturated collapsible loess, with a focus on unconfined compressive strength (UCS) and shear strength. Laboratory experiments systematically evaluated the effects of moisture content (14–22%), WSICP cementation solution (WCS) concentration (0–1.0 mol/L), and curing time (7–14 days) on the loess’s mechanical behavior. By cementing the soil particles and filling the pores, the calcium carbonate precipitation greatly improved the mechanical properties of the soil. The test results demonstrated that the WSICP technology could effectively increase the compressive and shear strength of loess, particularly in conditions of high moisture content (18–22%). The beneficial impact could be lessened, though, if the WCS concentration is too high under low moisture content conditions because metal cations interfere with the electrostatic interaction between soil particles. In situations with low moisture content, extending the curing time helps to increase compressive strength. The WSICP technique exhibits dual dependency on moisture and concentration, achieving optimal efficacy at 1.0 mol/L WCS and 18–22% moisture. Overall, WSICP technique offers a cost-effective, eco-friendly, and efficient way to ameliorate collapsible loess while also offering experimental and theoretical support for related engineering practice.